lncRNA IGKJ2‐MALLP2 suppresses LSCC proliferation, migration, invasion, and angiogenesis by sponging miR‐1911‐3p/p21 - Cao, Jing; Yang, Zhenming; An, Ran; Zhang, Jiarui; Zhao, Rui; Li, Wenjing; Xu, Licheng; Sun, Yanan; Liu, Ming; Tian, Linli (Cancer science, 2020)
Because advanced laryngeal squamous cell carcinoma (LSCC) is diagnosed as a malignant tumor with a poor prognosis, the associated mechanisms still need to be further investigated. As key players in the development and progression of LSCC, lncRNAs have attracted increasing attention from many researchers. In this study, a novel lncRNA termed IGKJ2‐MALLP2 was identified and investigated for its effects on the development of LSCC. IGKJ2‐MALLP2 expression was confirmed by RT‐qPCR in 78 pairs of tissues and human laryngeal carcinoma cell lines. The results of this study showed that the expression of IGKJ2‐MALLP2 was reduced in LSCC tissues and displayed close relationships with tumor stage, lymph node metastasis, and clinical stage. Using a dual‐luciferase reporter assay, the ability of miR‐1911‐3p to bind both IGKJ2‐MALLP2 and p21 mRNA was demonstrated. IGKJ2‐MALLP2 could upregulate p21 expression by competitively binding miR‐1911‐3p. Moreover, IGKJ2‐MALLP2 effectively hindered the invasion, migration, and proliferation of AMC‐HN‐8 and TU212 tumor cells. Furthermore, its high expression could hinder the secretion of VEGF‐A and suppress angiogenesis. As revealed by the results of in vitro experiments, IGKJ2‐MALLP2 overexpression could restrict tumor growth and blood vessel formation in a xenograft model of LSCC. As indicated from the mentioned findings, IGKJ2‐MALLP2, which mediates p21 expression by targeting miR‐1911‐3p, was capable of regulating LSCC progression and could act as an underlying therapeutic candidate to treat LSCC. LncRNA IGKJ2‐MALLP2 restricts the development of laryngeal squamous cell carcinoma by competitively binding miRNA‐1911‐3p to promote the expression of p21. And it also suppresses the secretion of VEGF‐A in vitro and limits the angiogenesis activities in vitro and in vivo. The number of blood vessels is decreased in the tumors over‐expressing lncRNA IGKJ2‐MALLP2.